Macrophage Migration Inhibitory Factor in Clinical Kidney Disease - Bruchfeld, Annette; Wendt, Mårten; Miller, Edmund J. (Frontiers in Immunology, 2016)
Macrophage migration inhibitory factor (MIF) is a pro-inflammatory cytokine implicated in acute and chronic inflammatory conditions including sepsis, autoimmune disease, atherogenesis, plaque instability and pulmonary arterial hypertension (PAH). MIF in plasma and urine is significantly elevated in patients with Acute Kidney injury (AKI) and elevated MIF in serum is associated with markers of oxidative stress, endothelial dysfunction, arterial stiffness and markers of myocardial damage in Chronic Kidney disease (CKD). Furthermore MIF seems to be involved in vascular processes and cardiovascular disease associated with CKD, glomerulonephritis, autosomal dominant polycystic kidney disease and possibly also in progression to renal failure. Moreover, in active ANCA-associated vasculitis plasma MIF-levels have been shown to be significantly elevated as compared with samples from patients in remission. A significant difference in the genotype frequency of high production MIF -173 G/C genotype has been found in end-stage renal disease (ESRD), compared to controls. Inhibition of MIF in a diabetic nephropathy model ameliorated blood glucose and albuminuria and in a model of adult polycystic kidney disease cyst growth was delayed. Preclinical studies support a potential therapeutic role for MIF in AKI and in a number of chronic kidney diseases whereas these data in human disease are still observational. Future interventional studies are needed to delineate the role of MIF as a treatment target in clinical kidney disease. Keywords: MIF, , AKI, CKD, glomerulonephritis, vasculitis, MIF gene polymorphism, diabetic nephropathy, ADPKD